REPRESENTATION OF INDONESIAN CULTURE THROUGH SOCIAL MEDIA AS AN EFFORT TO PRESERVE LOCAL CULTURE: CONTENT ANALYSIS OF TIKTOK ACCOOUNT KIKI NASUTION @sabda.bumi - Nur Husniyatul Adyani; Mega Alif Marintan; Toti Nova Amalia (Vol. 3 No. 1 (2025): Proceeding of International Conference on Cultures & Languages 2025, 2025)
Abstracts : The phenomenon of globalization presents a significant challenge to a nation's cultural resilience. Indonesia, a country rich in local cultural diversity, faces the risk of losing its cultural wealth if there are no adaptive conservation efforts. In this context, social media, particularly TikTok, presents a strategic opportunity to counter the trend of cultural homogenization. The platform offers creators the opportunity to represent local culture in an engaging and accessible way to a diverse community, packaged in digital content. This study aims to identify the form of Indonesian cultural representation on TikTok creator accounts, analyze the cultural values that appear in the content produced by @sabda.bumi creators, and explore how the contribution of cultural content on TikTok can help implement cultural resilience efforts and improve people's digital literacy. The method used in this study is a descriptive qualitative approach that identifies patterns, themes, and relationships within content from TikTok creators, specifically Kiki Nasution, through content analysis. The study's results show that Kiki Nasution's account content has a distinctive focus and approach in representing Indonesian culture through social media. This research also demonstrates that the presence of cultural content on TikTok serves not only as entertainment but also as a form of culture-based digital literacy, directly contributing to cultural resilience. This creator has proven to be able to make TikTok an alternative media for cultural preservation that adapts to digital dynamics, while building cultural awareness among the younger generation.